Building Teacher Performance Based Islam Religious Values - Ulfah, Maria (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
Islam provides a major place for human life. Because basically every child from birth has carried the fitrah of Religion, if they get a good Islamic Religious Education then they will become religious people, but otherwise if the religious seeds they carry are not nurtured and nurtured, they will become people who are far from religion. The purpose of this research is to find out the religious values that explicitly shape the teacher's personality. For that, a qualitative research and descriptive analysis were conducted. The findings in this study indicate that in general the teachers have performed, although still in the minimum scope. However, the role of Islamic religious values ​​that they have practiced has had a major influence on life as a teacher. Of course, an exemplary teacher must have religious values ​​such as gratitude, patience, endeavor, trust and humility because these 5 indicators are the intrinsic keys to success in becoming a teacher.